2012
DOI: 10.1186/1471-2458-12-627
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health news disseminated in the print media in developing countries: a case study in Iran

Abstract: BackgroundMass media play an important role in keeping people up-to-date with the latest health news. This study aims at investigating the quality of health news disseminated in the print media, its course of production and factors affecting its quality.MethodsIn the quantitative section of the study, 410 health-related news items, published during a six-month span in the Iranian public press, underwent content analysis. In the qualitative section, focus group discussions were held with journalists, editors-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…This may be attributed to journalists’ perception of research as dry and boring, in addition to difficulties and time limitations to access, understand and translate research studies. Similar findings were reported by Voss (2002), Larsson et al, (2003) and Ashorkhani et al, (2012) linking difficulties in evidence based health reporting to time pressures and the rigid nature of evidence [ 17 , 19 , 20 ]. The limited use of evidence in health reporting was also found in two international health information television programs as reported in Korownyk et al (2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This may be attributed to journalists’ perception of research as dry and boring, in addition to difficulties and time limitations to access, understand and translate research studies. Similar findings were reported by Voss (2002), Larsson et al, (2003) and Ashorkhani et al, (2012) linking difficulties in evidence based health reporting to time pressures and the rigid nature of evidence [ 17 , 19 , 20 ]. The limited use of evidence in health reporting was also found in two international health information television programs as reported in Korownyk et al (2014).…”
Section: Discussionsupporting
confidence: 83%
“…Literature suggests many factors hindering the dissemination and the accurate reporting of health research in the media. These factors include journalists’ lack of time, limited publishable time, lack of science background, difficulties in understanding jargons, complexities of health issues, commercial pressures and problems with finding and using resources [ 17 , 19 , 20 ]. Researchers also worry about the inaccuracy and sensationalism of their work by the media [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a content analysis was conducted to investigate the coverage of health issues in two of the leading newspapers in Nigeria between a 24-months duration that revealed that health stories are given very less space and position (Onyeizu & Binta, 2014). Ashoorkhani, Gholami, Maleki, Nedjat, Mortazavi and Majdzadeh (2012) examined the quality of health news published in newspapers and the elements affecting its circulation in developing nations. These studies mentioned above lack the critical investigation of people's perceptions about the quality of health messages and the political components responsible for misusing their power by hijacking television health content.…”
Section: Televised Health Messagesmentioning
confidence: 99%
“…General populace receives its health-related information from mass media. [ 1 ] Using these media, outlets play an important role in transfer of information and improving society's knowledge and attitude and can also play an important role in controlling the prevalence of diseases in society. [ 2 ] Today's society that despite increased importance of electronic media have managed to stay as strong as ever in printed press role in informing the populace.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the previous literature showed that various studies have been conducted on content analysis of medical and health-related information on electronic and printed media in Iran and other countries, and among various media, newspapers have been one of the favorite forms of media in these studies. [ 1 7 9 10 11 14 16 ] However, there are no content analysis studies on pediatric health information in Iran. Given the fact that most people use public publications, mass media, and internet to obtain their health-related information[ 17 18 ] and given the importance of health information, especially pediatric health information, this study aims to perform a content analysis on the pediatric health information published in widely circulated Iranian newspapers, the most important published massages, the topic trends of the message have been published and empty topic areas.…”
Section: Introductionmentioning
confidence: 99%